Loamy sand soil approaches organic carbon saturation after 37 years of conservation tillage. (14th April 2020) - Novak, J.M.; Watts, D.W.; Bauer, P.J.; Karlen, D.L.; Hunt, P.G.; Mishra, U.
Abstract: Conservation tillage is reported to increase soil organic carbon (SOC) and total nitrogen (TN) contents, but long‐term (>30 yr) field results quantifying the responses in Coastal Plain Ultisols are sparse. The distribution, accumulation, and topsoil storage of SOC and TN after 37 yr of crop production using conventional (CvT) or conservation tillage (CnT) on a Norfolk loamy sand (fine‐loamy, kaolinitic, thermic, Typic Kandiudults) were quantified. Soil samples were collected annually from the 0−5‐, 5−10‐, and 10−15‐cm depth increments beneath corn ( Zea mays L.), soybean [ Glycine max (L.) Merr.], and cotton ( Gossypium hirsutum L.) crops. Overall, SOC and TN accumulation in the 0−5‐cm depth were highest for Norfolk soil under CnT. Focusing on total long‐term changes for the 0−15‐cm sampling depth beneath various corn crops shows that CnT and CvT sequestered 24.7 and 21.4 Mg C ha −1, respectively. Between 1978 and 2016, there was a highly significant ( P  < .0001) exponential increase in SOC within the top 5‐cm soil depth. However, the exponential curves began to plateau suggesting the Norfolk topsoil was approaching its organic carbon (OC) storage capacity. These field measurements strongly indicate that additional topsoil SOC increases with current tillage and crop management practices are limited.